Synthesis process of high-molecular-weight unsaturated polyether
Through a two-step process, the molecular weight distribution and double bond retention rate of high molecular weight unsaturated polyethers are successfully improved by using the combination of alkaline catalysis and acidic additives and bimetallic cyanide complexing catalysts, and the molecular weight distribution and double bond retention rate of high molecular weight unsaturated polyethers are solved in the prior art Ether quality problems meet the high performance requirements of sealant.
Patent Information
- Application Number
- CN202411535751.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
AI Technical Summary
It is difficult to prepare high molecular weight unsaturated polyether products with narrower molecular weight distribution, higher double bond retention and fewer impurities, which affect the structure and quality of the polyether.
Using a two-step process, firstly, the low molecular weight polyether is synthesized by alkaline catalysis and refined, and then further polymerized with an acid additive catalyst and a bimetallic cyanide complexing catalyst to control the reaction conditions and the amount of catalyst to obtain high molecular weight unsaturated poly ether.
The polyether has a narrower molecular weight distribution, higher double bond retention and fewer impurities, which meets the high performance requirements for sealant use.
Smart Images

Figure BDA0005111499590000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethers, and in particular to a synthesis process of high molecular weight unsaturated polyethers. Background Art
[0002] Unsaturated polyethers are mainly divided into two types according to their applications. Among them, the most widely used is polyoxyethylene unsaturated polyether, which is mainly produced by ring-opening polymerization of alcohols containing unsaturated double bonds and ethylene oxide, and is used in the manufacture of carboxylic acid water reducers and non-ionic surfactants. The other type is to produce products with special properties by reacting special groups with unsaturated bonds, such as reacting with hydrogen-containing silicone oil to produce special silicone oil, etc. For example, straight-chain polyethers with double bond end-capping at both ends can be used as the main raw material for silane-terminated polyether sealants.
[0003] The production processes of polyethers terminated with double bonds on both sides are mainly propylene glycol polyether diol double bond termination and polyether monool double bond termination using alcohols containing unsaturated double bonds. Among them, the process of polyethers prepared with unsaturated alcohols as initiators has a higher double bond retention rate and meets the requirements of silane-modified polyether sealants and is therefore valued.
[0004] When double metal cyanide complex catalyst (DMC) is used to catalyze the preparation of polyethers with higher molecular weight, the side reaction rate is extremely low, the degree of retention of the polyether structure is higher, and the original double bond structure of the polyether is not destroyed. It has higher practical value in the synthesis of raw material polyether for sealant. At the same time, the post-treatment of crude polyether is also particularly important, which affects important indicators such as metal ion and moisture content, pH value and chromaticity of polyether products. Therefore, improving the technical level of polyether post-treatment can maintain the structure of polyether to a great extent, and the quality of polyether products will also improve accordingly. Based on the current existing technology, how to prepare high molecular weight unsaturated polyether products with narrower molecular weight distribution, higher double bond retention rate and less impurities is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above problems, the present invention provides a synthesis process of high molecular weight unsaturated polyether.
[0006] The present invention provides a synthesis process of a high molecular weight unsaturated polyether, comprising the following steps:
[0007] (1) adding a first initiator to a reaction system, replacing with an inert gas, adding a basic catalyst, reacting to completely dissolve the basic catalyst, and adding a second initiator;
[0008] (2) continuing the inert gas replacement, feeding the first epoxy monomer at the first reaction temperature, and continuing the reaction until the reaction is complete after the feeding is completed to obtain a first low molecular weight polyether;
[0009] (3) subjecting the first low molecular weight polyether to a water-adding and temperature-raising reaction, neutralization, water removal, and a first refining in sequence, and then discharging and filtering a solid residue to obtain a second low molecular weight polyether;
[0010] (4) mixing the second low molecular weight polyether and the solution of the acidic auxiliary catalyst, then adding the double metal cyanide complex catalyst, and starting heating, stirring, and vacuum;
[0011] (5) Turn off the vacuum, control the second reaction temperature, introduce epoxy monomer for aging, then cool down and perform vacuum degassing.
[0012] Optionally, step (5) obtains a crude polyether, and the synthesis process further comprises the following steps after step (5):
[0013] (6) After cooling the crude polyether, alkalization, secondary refining, heating dehydration, and filtration are performed in sequence to obtain a high molecular weight unsaturated polyether.
[0014] Optionally, the acidic auxiliary catalyst in step (4) is fluorosilicic acid and / or fluoroboric acid.
[0015] Optionally, the mass fraction of the solution of the acidic auxiliary catalyst in step (4) is 5 to 15%, and the amount of the solution of the acidic auxiliary catalyst is 1 to 10 ppm of the designed total mass of the high molecular weight unsaturated polyether;
[0016] The dosage of the double metal cyanide complex catalyst is 15 to 65 ppm of the designed total mass of the high molecular weight unsaturated polyether.
[0017] Optionally, in step (4), the solution of the second low molecular weight polyether and the acidic auxiliary catalyst is mixed for 20 to 60 minutes before adding the double metal cyanide complex catalyst.
[0018] Optionally, the step (5) of introducing epoxy monomer for aging comprises the following steps performed in sequence:
[0019] A second epoxy monomer is introduced to perform a first aging process, a third epoxy monomer is introduced to perform a second aging process, and a fourth epoxy monomer is introduced to perform a third aging process.
[0020] Optionally, the first epoxy monomer in step (2), the second epoxy monomer in step (5), the third epoxy monomer, and the fourth epoxy monomer are each ethylene oxide and / or propylene oxide.
[0021] Optionally, in step (2), the first epoxy monomer is propylene oxide; in step (5), the second epoxy monomer is propylene oxide, the third epoxy monomer is a mixture of ethylene oxide and propylene oxide, and the fourth epoxy monomer is propylene oxide;
[0022] Based on the designed total mass of the high molecular weight unsaturated polyether, the mass proportion of ethylene oxide in the third epoxy monomer is 0 to 35%.
[0023] Optionally, in step (1), the first initiator and the second initiator are each one or more selected from allyl alcohol, methacrylic alcohol, N-methylallylamine, and 3-butene-1-ol;
[0024] Based on the molecular weight of the high molecular weight unsaturated polyether being 5000-15000, the molecular weight of the first initiator accounts for 0.05-0.75% of the molecular weight of the high molecular weight unsaturated polyether, and the molecular weight of the second initiator accounts for 0.02-1.00% of the molecular weight of the high molecular weight unsaturated polyether.
[0025] Optionally, in step (1), the first initiator is allyl alcohol, and the second initiator is 3-butene-1-ol.
[0026] Optionally, the filtration in step (6) is performed by pressure filtration using a glass fiber filter membrane.
[0027] Optionally, the alkaline catalyst in step (1) is one or more selected from metallic potassium, metallic sodium, sodium methoxide, potassium hydroxide, and sodium hydroxide;
[0028] The amount of the alkaline catalyst added in step (1) is 0.05 to 1.00% of the total mass of the second low molecular weight polyether added in step (3).
[0029] Beneficial effects:
[0030] The invention synthesizes a high molecular weight unsaturated polyether through a two-step process, firstly adopts alkaline catalysis to synthesize a low molecular weight polyether and purifies it, then adopts an acidic auxiliary catalyst and a double metal cyanide complex catalyst to cooperate with each other to further polymerize the low molecular weight polyether, and finally obtains a high molecular weight unsaturated polyether with a narrower molecular weight distribution, a higher double bond retention rate and less impurities. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below through examples. Through these examples, the features and advantages of the present invention will become clearer and more specific.
[0032] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0033] In the present invention, the term "designed total mass of high molecular weight unsaturated polyether" refers to the total mass of all initiators and epoxy monomers in terms of feed when synthesizing the high molecular weight unsaturated polyether.
[0034] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0035] The present invention provides a synthesis process of a high molecular weight unsaturated polyether, comprising the following steps:
[0036] (1) adding a first initiator to a reaction system, replacing with an inert gas, adding a basic catalyst, reacting to completely dissolve the basic catalyst, and adding a second initiator;
[0037] (2) continuing the inert gas replacement, feeding the first epoxy monomer at the first reaction temperature, and continuing the reaction until the reaction is complete after the feeding is completed to obtain a first low molecular weight polyether;
[0038] (3) subjecting the first low molecular weight polyether to a water-adding and temperature-raising reaction, neutralization, water removal, and a first refining in sequence, and then discharging and filtering a solid residue to obtain a second low molecular weight polyether;
[0039] (4) mixing the second low molecular weight polyether and the solution of the acidic auxiliary catalyst, then adding the double metal cyanide complex catalyst, and starting heating, stirring, and vacuum;
[0040] (5) Turn off the vacuum, control the second reaction temperature, introduce epoxy monomer for aging, then cool down and perform vacuum degassing.
[0041] In one embodiment of the above-mentioned synthesis process of the present invention, step (5) obtains a crude polyether, and the synthesis process further comprises the following steps after step (5):
[0042] (6) After cooling the crude polyether, alkalization, secondary refining, heating dehydration, and filtration are performed in sequence to obtain a high molecular weight unsaturated polyether.
[0043] In another embodiment of the aforementioned synthesis process of the present invention, the acidic auxiliary catalyst in step (4) is fluorosilicic acid and / or fluoroboric acid.
[0044] The invention synthesizes a high molecular weight unsaturated polyether through a two-step process, firstly adopts an alkaline catalyst to synthesize a low molecular weight polyether and performs neutralization and purification, then adopts fluorosilicic acid and / or fluoroboric acid as an acidic auxiliary catalyst to cooperate with a double metal cyanide complex catalyst (DMC catalyst) for catalysis, further polymerizes the low molecular weight polyether into a finished product polyether and performs purification, and finally obtains a high molecular weight unsaturated polyether.
[0045] Specifically, after the preparation of the initiator solution and the intermediate crude polyether is completed through steps (1) and (2), the first initiator can be added to a closed reactor with a cooling coil, replaced with industrial N2 for 3 to 5 times, and the alkaline catalyst cut into small pieces is added. After the alkaline catalyst is completely dissolved, part of the gas in the reactor can be discharged and the second initiator is added. After the temperature is raised to the required temperature, a certain amount of the first epoxy monomer is added and reacted to obtain a crude polyether intermediate, i.e., the first low molecular weight polyether.
[0046] Step (3) completes the purification of the crude polyether intermediate, transfers the crude polyether intermediate, i.e., the first low molecular weight polyether, to a neutralization reaction kettle (which may be a normal pressure glass reaction kettle), adds an appropriate amount of deionized water, heats the reaction for a certain period of time, then adds a neutralizer for neutralization, removes the water in the system, adds a refining agent to further absorb the trace metal ions in the polyether, and then filters out the solid residue in the system to obtain a polyether intermediate, i.e., the second low molecular weight polyether.
[0047] Steps (4) and (5) are used to synthesize a high molecular weight unsaturated polyether. The second low molecular weight polyether is transferred into a clean reaction kettle, a solution of an acidic co-catalyst is added and mixed for a certain period of time, and then a DMC catalyst is added. The temperature is raised to a pre-reaction temperature under vacuum, the vacuum is turned off, and a quantitative amount of epoxy monomer is added. After the monomer feeding is completed and the reaction is complete, trace volatile components in the system are removed under vacuum to obtain a high molecular weight crude polyether.
[0048] Step (6) purifies the crude polyether with high molecular weight, transfers the crude polyether to a refining reactor (which may be a glass neutralization reactor), puts in an aqueous NaOH solution, adds a polyether refining agent after alkalization for half an hour, heats and removes water from the polyether, and finally obtains the finished polyether by filtration. According to small-scale experiments and analysis, the high molecular weight unsaturated polyether produced by the process of the present invention has a narrower molecular weight distribution, a higher double bond retention rate, and a total metal ion determination value of less than 3ppm, which fully meets the requirements of the end-capping process.
[0049] In the two-step synthesis process of the present invention, the polyether synthesis adopts alkaline catalysis to prepare the intermediate and then uses DMC catalyst to synthesize the finished polyether. In order to reduce the impact on the final polyether product, after the intermediate is prepared, before adding the DMC catalyst in step (4), a solution of an acidic auxiliary catalyst is added to play the role of a stabilizer, neutralize the trace alkali brought in the polyether polymerization process, and make some metal catalysts lose activity, thereby achieving a stabilizing effect, so as to synthesize a high molecular weight unsaturated polyether with excellent performance. In particular, when fluorosilicic acid and / or fluoroboric acid are used as the acidic auxiliary catalyst, the acidic auxiliary catalyst can synergistically enhance the performance with the DMC catalyst, and can improve the performance of the polyether product in many aspects, and finally obtain a high molecular weight unsaturated polyether product with narrower molecular weight distribution, higher double bond retention rate and less impurities. The molecular weight of the polyether product can be but not limited to 1000-20000.
[0050] In one embodiment of the above-mentioned synthesis process of the present invention, the mass fraction of the solution of the acidic auxiliary catalyst in step (4) is 5-15%, and the amount of the solution of the acidic auxiliary catalyst is 1-10 ppm of the designed total mass of the high molecular weight unsaturated polyether;
[0051] The dosage of the double metal cyanide complex catalyst is 15 to 65 ppm of the designed total mass of the high molecular weight unsaturated polyether.
[0052] It should be noted that the mass fraction of the solution of the acidic auxiliary catalyst can be specifically 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% and the like; the dosage of the solution of the acidic auxiliary catalyst can be 1 to 20 ppm of the designed total mass of the high molecular weight unsaturated polyether, specifically 2ppm, 3ppm, 4ppm, 5ppm, 6ppm, 7ppm, 8ppm, 9ppm, 10ppm, 11ppm, 12ppm, 13ppm, 14ppm, 15ppm, 16ppm, 17ppm, 18ppm, 19ppm, 20ppm and the like of the designed total mass of the high molecular weight unsaturated polyether; the dosage of the DMC catalyst can preferably be 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, 55ppm, 60ppm, 65ppm of the designed total mass of the high molecular weight unsaturated polyether.
[0053] In the synthesis process of the present invention, by controlling the mass fraction and dosage of the solution of the acidic auxiliary catalyst and the dosage of the DMC catalyst as above, it is beneficial to prepare a high molecular weight unsaturated polyether with better performance, so that the molecular weight distribution of the polyether product is narrower, the double bond retention rate is higher, and the impurities are less.
[0054] In another embodiment of the above synthesis process of the present invention, in step (4), the second low molecular weight polyether and the solution of the acidic auxiliary catalyst are mixed for 20 to 60 minutes before adding the double metal cyanide complex catalyst.
[0055] It should be noted that, after years of research and development experiments, the inventors of the present application have found that when fluorosilicic acid and / or fluoroboric acid are used as acidic auxiliary catalysts, the mixing time of the second low molecular weight polyether and the acidic auxiliary catalyst solution has an important influence on the molecular weight distribution, double bond retention rate, etc. of the final synthesized polyether product. If the mixing time of the second low molecular weight polyether and the acidic auxiliary catalyst solution is too short or too long, and then the same amount of DMC catalyst is added, the performance of the final finished polyether is reduced. The DMC catalyst is added after the second low molecular weight polyether and the acidic auxiliary catalyst solution are mixed for 20 to 60 minutes, and the molecular weight distribution of the final polyether product is narrower, the double bond retention rate is higher, and there are fewer impurities.
[0056] In one embodiment of the above synthesis process of the present invention, the step (5) of introducing the epoxy monomer for aging comprises the following steps performed in sequence:
[0057] A second epoxy monomer is introduced to perform a first aging process, a third epoxy monomer is introduced to perform a second aging process, and a fourth epoxy monomer is introduced to perform a third aging process.
[0058] It should be noted that the second epoxy monomer, the third epoxy monomer, and the fourth epoxy monomer may be the same or different epoxy monomers.
[0059] In one embodiment of the above synthesis process of the present invention, the first epoxy monomer in step (2), the second epoxy monomer in step (5), the third epoxy monomer, and the fourth epoxy monomer are each ethylene oxide and / or propylene oxide.
[0060] It should be noted that when the first epoxy monomer in step (2) is propylene oxide, step (3) obtains propylene oxide polyether (polypropylene oxide), and when the first epoxy monomer in step (2) is ethylene oxide, step (3) obtains ethylene oxide polyether (polyethylene oxide). If the first epoxy monomer, the second epoxy monomer, the third epoxy monomer, and the fourth epoxy monomer are the same epoxy monomers, if they are all ethylene oxide, the polyether product is ethylene oxide polyether, and if they are all propylene oxide, the polyether product is propylene oxide polyether. The first epoxy monomer, the second epoxy monomer, the third epoxy monomer, and the fourth epoxy monomer can be different monomers. By adjusting the monomers and the order of feeding, a variety of polyether products such as random copolymerization and block copolymerization can be prepared.
[0061] In a preferred embodiment of the above synthesis process of the present invention, in step (2), the first epoxy monomer is propylene oxide; in step (5), the second epoxy monomer is propylene oxide, the third epoxy monomer is a mixture of ethylene oxide and propylene oxide, and the fourth epoxy monomer is propylene oxide;
[0062] Based on the designed total mass of the high molecular weight unsaturated polyether, the mass proportion of ethylene oxide in the third epoxy monomer is 0 to 35%.
[0063] In this preferred embodiment, the mass proportion of ethylene oxide in the third epoxy monomer can be 5%, 10%, 15%, 20%, 25%, 30%, 35%. The structure of the high molecular weight unsaturated polyether can be an ABA type structure, the initiator first reacts with propylene oxide to form a certain molecular weight propylene oxide polyether, and then is mixed with two catalysts in step (4), and then polymerized with propylene oxide monomer in step (5) and matured until the reaction is complete, and then randomly copolymerized with the mixture of propylene oxide and ethylene oxide and matured completely, and finally ring-opened polymerized with propylene oxide monomer and matured completely to obtain a PO-(EO / PO)-PO block structure polyether product, PO represents a propylene oxide ring-opening polymerized segment, EO represents an ethylene oxide ring-opening polymerized segment, and EO / PO represents an intermediate segment of ethylene oxide and propylene oxide mixed (random copolymerization) after ring opening. The molecular weight of the polyether product finally obtained may be, but not limited to, 5000 to 12000, and can be used as a polyether raw material for preparing sealants.
[0064] In the synthesis process of the present invention, by controlling the monomer types of the first epoxy monomer, the second epoxy monomer, the third epoxy monomer, and the fourth epoxy monomer as above, and feeding them in the above order, the prepared polyether product with a specific segment structure mainly composed of propylene oxide has very excellent performance, a narrower molecular weight distribution, a higher double bond retention rate and fewer impurities.
[0065] In another embodiment of the above synthesis process of the present invention, in step (1), the first initiator and the second initiator are each selected from one or more of allyl alcohol, methyl propylene alcohol, N-methyl allylamine, and 3-butene-1-ol;
[0066] Based on the molecular weight of the high molecular weight unsaturated polyether being 5000-15000, the molecular weight of the first initiator accounts for 0.05-0.75% of the molecular weight of the high molecular weight unsaturated polyether, and the molecular weight of the second initiator accounts for 0.02-1.00% of the molecular weight of the high molecular weight unsaturated polyether.
[0067] In step (1), the first initiator and the second initiator can each be selected from the above-mentioned unsaturated alcohols or amines containing double bonds.
[0068] In a preferred embodiment of the above synthesis process of the present invention, in step (1), the first initiator is allyl alcohol, and the second initiator is 3-butene-1-ol.
[0069] The initiator of polyether is generally a small molecule alcohol with unsaturated double bonds. We select allyl alcohol and 3-butene-1-ol as the first initiator and the second initiator respectively from the perspective of performance and cost. Considering that the final polyether product may be used as a raw material for silane-modified polyether sealant, a high double bond retention rate and double bond reactivity are required, allyl alcohol and 3-butene-1-ol are preferably used as the initiators of unsaturated polyether. When these two initiators are used in combination, the prepared polyether product not only has a high double bond retention rate, but also has high reactivity in the process of preparing the sealant.
[0070] As a variation of the embodiment, the first initiator and the second initiator can be the same, and can be allyl alcohol. In this case, although the polyether product finally prepared has a narrow molecular weight distribution, a high double bond retention rate, and a low impurity content, the reaction activity is low in the process of preparing the sealant. In the synthesis process of the present invention, in step (1), allyl alcohol is used as the first initiator added first, and 3-butene-1-ol is used as the second initiator added later, and the two initiators are used in combination. According to the subsequent steps in the synthesis process of the present invention, fluorosilicic acid and / or fluoroboric acid are used as acidic auxiliary catalysts in combination with DMC catalysts, so that the final polyether product not only has a narrow molecular weight distribution, a high double bond retention rate, and a low impurity content, but also has high reaction activity in the process of preparing the sealant.
[0071] In another embodiment of the above synthesis process of the present invention, the filtration in step (6) is performed by pressure filtration using a glass fiber filter membrane.
[0072] After the polyether product is synthesized, the catalyst component needs to be removed. If the impurity content in the product is extremely low, it will not affect the subsequent synthesis. For polyethers that reach a certain high molecular weight, it is difficult for ordinary filtering methods to achieve good filtering effects due to the constraints of its viscosity and other aspects. The glass fiber filter membrane can be a high-purity glass fiber filter membrane, etc. The high-purity glass fiber filter membrane has a high porosity and good filtering performance, so as to better remove insoluble impurities and improve the purity of the polyether. In addition, when filtering high-molecular-weight polyethers with a certain viscosity, the high-purity glass fiber filter membrane can show good chemical stability and thermal stability, can withstand a certain temperature and chemical environment, and will not bring any negative impact to the polyether, which makes it highly applicable when processing organic compounds such as polyethers. Therefore, the use of high-purity glass fiber filter membranes for filtration can well filter out impurities such as trace catalyst residues in the product, and keep the polyether in excellent performance, and finally obtain a finished polyether with a narrower molecular weight distribution, a higher double bond retention rate and fewer impurities.
[0073] In one embodiment of the above-mentioned synthesis process of the present invention, the alkaline catalyst in step (1) is one or more selected from metallic potassium, metallic sodium, sodium methoxide, potassium hydroxide, and sodium hydroxide;
[0074] The amount of the alkaline catalyst added in step (1) is 0.05 to 1.00% of the total mass of the second low molecular weight polyether added in step (3).
[0075] It should be noted that the alkaline catalyst in step (1) can be one or more selected from the group consisting of simple substances, oxides, hydroxides, and alcoholates of alkali metals and alkaline earth metals, and is particularly preferably metallic potassium; the amount of the alkaline catalyst is preferably 0.10 to 0.25% of the total mass of the second low molecular weight polyether obtained in step (3). When the alkaline catalyst in step (1) is preferably metallic potassium and the amount is controlled as above, the metallic potassium not only has a higher catalytic activity and fewer reaction treatment steps, but also uses metallic potassium as an alkaline catalyst and then synthesizes according to the synthesis process of the present invention, which can further improve the performance of the synthesized polyether product, making the molecular weight distribution of the polyether product narrower, the double bond retention rate higher, and the impurities less.
[0076] It should be noted that the water-adding and temperature-raising reaction in step (3) can be carried out as follows:
[0077] Add water and heat to 75-95° C. to react for 40 min-2 h, wherein the mass of the added water may account for 1-15% of the mass of the first low molecular weight polyether obtained in step (2) based on the output;
[0078] For propylene oxide polyether with a molecular weight of about 400, 10% deionized water can be added and reacted at 90°C for 1 hour.
[0079] The neutralization process in step (3) can be carried out as follows:
[0080] A neutralizing agent is added for neutralization. The neutralizing agent may be one or more selected from sulfuric acid, phosphoric acid, pyrophosphoric acid, and adipic acid, or may be one or more selected from acid salts of sulfuric acid, phosphoric acid, pyrophosphoric acid, and adipic acid. Generally, phosphoric acid or an aqueous solution of adipic acid may be used as the neutralizing agent. The neutralization may be carried out at 75 to 100° C. for 1 to 2 hours.
[0081] In step (3), water removal can be carried out as follows:
[0082] The water removal can be carried out by vacuum dehydration at 105-125° C. to reduce the water content to less than 0.02%. The dehydration process can generally be heated up for dehydration after the neutralization reaction is completed. The dehydration temperature should not be too high. In the later stage of dehydration, high-purity nitrogen can be bubbled at the bottom of the reactor to improve the dehydration efficiency. Due to the requirements of the DMC catalyst catalytic process in step (4), the water content must be less than 0.02%.
[0083] In step (3), the first purification can be carried out as follows:
[0084] A first refining agent is added for first refining. The first refining agent may be magnesium silicate and / or aluminum silicate. The mass of the first refining agent may account for 0.01 to 1.0% of the total mass of the high molecular weight unsaturated polyether obtained from step (6). The first refining may be carried out at 105 to 125° C., such as 120° C., for 1.5 to 3 hours.
[0085] In step (3), the solid residue can be filtered as follows:
[0086] Various types of filters can be selected for the filtration process, and the solid residue in the polyether is required to be completely filtered. The polyether intermediate after filtration is required to be slightly acidic, and the pH value can be between 6 and 7. After filtering the solid residue, an intermediate, i.e., a second low molecular weight polyether, is obtained. The molecular weight of the intermediate can be, but not limited to, 200 to 600, and preferably about 200, 400, 500, etc. The molecular weight design of the intermediate is related to the reactor specification and the material growth ratio of the designed polymerization process.
[0087] After the above-mentioned steps of adding water and heating the reaction, neutralizing, removing water, first refining, and filtering the solid residue in step (3), the polyether intermediate has completed the refining process.
[0088] In step (6), alkalization can be carried out as follows:
[0089] An alkalizing agent solution is added for alkalization, wherein the alkalizing agent solution may be an aqueous NaOH solution and / or an aqueous KOH solution, and the amount of the alkalizing agent solution used may be 10 to 1000 ppm of the designed total mass of the high molecular weight unsaturated polyether; the alkalization may be carried out at 25 to 95° C. for 0.5 to 1.5 h; the mass fraction of the alkalizing agent solution used during the alkalization may generally be 1 to 15%, and a 10% aqueous solution may be added at 20 ppm, 30 ppm, 50 ppm, 70 ppm, 90 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, or 1000 ppm of the designed total mass of the high molecular weight unsaturated polyether.
[0090] In step (6), the second purification can be carried out as follows:
[0091] A second refining agent can be added for a second refining of 0.5 to 2.0 hours, preferably 1.0 to 1.5 hours. Alternatively, a dehydration treatment can be directly performed after the second refining agent is added, and the refining process can be regarded as completed after the moisture content is qualified. The amount of the second refining agent can be 50 to 500 ppm of the designed total mass of the high molecular weight unsaturated polyether.
[0092] When heating and dehydrating in step (6), nitrogen bubbling can be started at 110-125°C to remove moisture.
[0093] The present invention is further described in detail by way of examples below, but the present invention is not limited thereto. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.
[0094] The high-purity glass fiber filter membrane used in the following examples is a QM-TN#1650 high-purity ultrafine quartz fiber filter cartridge produced by Qingdao Baolan Technology Co., Ltd.
[0095] Example 1
[0096] An unsaturated polyether with a molecular weight of 10,000 is prepared in a 5L polymerization reactor, comprising the following steps:
[0097] (1) Add 325 g of allyl alcohol to a clean reactor, start stirring, replace with N2 three times, then add 5 g of potassium metal, and allow the reaction to fully dissolve the potassium metal. If the material temperature rises sharply or exceeds 85°C, cool the reactant with cooling water to lower the temperature. Add 135 g of 3-butene-1-ol.
[0098] (2) Continue N2 replacement for 2 times, maintain the pressure in the reactor slightly higher than normal pressure, then introduce propylene oxide: 2540 g, maintain the reaction temperature at 110°C, feed time 5 hours, and continue the reaction for 2.5 hours after the end of feeding until the reaction is complete.
[0099] (3) The material was completely transferred to a 5L atmospheric pressure glass reactor, 300g of deionized water was added to the reactor, the temperature was raised to 90°C for reaction for 1 hour, 25g of 85% phosphoric acid was added, the temperature was maintained for neutralization for 1.5 hours, and then the temperature was raised to 120°C, and the water in the system was completely removed by vacuum. After the water content was analyzed to be less than 0.02%, the vacuum was broken with N2, and 5g of magnesium silicate refining agent was added to the reactor, the temperature was maintained for refining for 2 hours, and the material was discharged. The solid residue was filtered with a plate circulation filter or a Buchner funnel with filter paper to obtain a polyether intermediate.
[0100] (4) Add 120 g of the polyether intermediate and 0.01 g of a 10% fluorosilicic acid aqueous solution and mix for half an hour. Then add 0.125 g of a DMC catalyst and mix thoroughly. Then put the mixture into a clean reactor and start heating, stirring, and vacuum. Raise the temperature to 145°C.
[0101] (5) Turn off the vacuum, control the reaction temperature at 140-145°C, first introduce 480 g of propylene oxide, add the feed time for 1 hour, mature for 0.5 hour, then introduce a mixture of 450 g of ethylene oxide and 1350 g of propylene oxide, add the feed time for 3 hours, mature for 0.5 hour after the addition is completed, finally add 600 g of propylene oxide, add the feed time for 1.5 hours, mature for 1 hour, then cool to 110°C and start vacuum degassing for 30 minutes to remove unreacted volatile components to obtain a crude polyether.
[0102] (6) The crude polyether was transferred to a glass neutralization reactor, cooled to below 60°C, and then 0.5 g of a 10% NaOH aqueous solution was added. The reaction was maintained at 50-60°C for 1 hour for alkalization, and then 0.6 g of a magnesium silicate concentrate was added. The temperature was raised to 110°C for dehydration until the moisture content of the material was less than 0.02%, and the finished polyether was obtained by filter pressing with a high-purity glass fiber filter membrane.
[0103] Example 2
[0104] Unsaturated polyether was prepared according to the method of Example 1, except that:
[0105] In step (4), the fluorosilicic acid aqueous solution is replaced by a fluoroboric acid aqueous solution.
[0106] An unsaturated polyether with a molecular weight of 10,000 is prepared in a 5L polymerization reactor, comprising the following steps:
[0107] (1) Add 325 g of allyl alcohol to a clean reactor, start stirring, replace with N2 three times, then add 5 g of potassium metal, and allow the reaction to fully dissolve the potassium metal. If the material temperature rises sharply or exceeds 85°C, cool the reactant with cooling water to lower the temperature. Add 135 g of 3-butene-1-ol.
[0108] (2) Continue N2 replacement for 2 times, maintain the pressure in the reactor slightly higher than normal pressure, then introduce propylene oxide: 2540 g, maintain the reaction temperature at 110°C, feed time 5 hours, and continue the reaction for 2.5 hours after the end of feeding until the reaction is complete.
[0109] (3) The material was completely transferred to a 5L atmospheric pressure glass reactor, 300g of deionized water was added to the reactor, the temperature was raised to 90°C for reaction for 1 hour, 25g of 85% phosphoric acid was added, the temperature was maintained for neutralization for 1.5 hours, and then the temperature was raised to 120°C, and the water in the system was completely removed by vacuum. After the water content was analyzed to be less than 0.02%, the vacuum was broken with N2, and 5g of magnesium silicate refining agent was added to the reactor, the temperature was maintained for refining for 2 hours, and the material was discharged. The solid residue was filtered with a plate circulation filter or a Buchner funnel with filter paper to obtain a polyether intermediate.
[0110] (4) Add 120 g of the polyether intermediate and 0.01 g of a 10% fluoroboric acid aqueous solution and mix for half an hour. Then add 0.125 g of a DMC catalyst and mix thoroughly. Then put the mixture into a clean reactor and start heating, stirring, and vacuum. Heat to 145°C.
[0111] (5) Turn off the vacuum, control the reaction temperature at 140-145°C, first introduce 480 g of propylene oxide, add the feed time for 1 hour, mature for 0.5 hour, then introduce a mixture of 450 g of ethylene oxide and 1350 g of propylene oxide, add the feed time for 3 hours, mature for 0.5 hour after the addition is completed, finally add 600 g of propylene oxide, add the feed time for 1.5 hours, mature for 1 hour, then cool to 110°C and start vacuum degassing for 30 minutes to remove unreacted volatile components to obtain a crude polyether.
[0112] (6) The crude polyether was transferred to a glass neutralization reactor, cooled to below 60°C, and then 0.5 g of a 10% NaOH aqueous solution was added. The reaction was maintained at 50-60°C for 1 hour for alkalization, and then 0.6 g of a magnesium silicate concentrate was added. The temperature was raised to 110°C for dehydration until the moisture content of the material was less than 0.02%, and the finished polyether was obtained by filter pressing with a high-purity glass fiber filter membrane.
[0113] Example 3
[0114] Unsaturated polyether was prepared according to the method of Example 1, except that:
[0115] The high-purity glass fiber membrane filter press in step (6) is replaced by glass sand core filtration.
[0116] An unsaturated polyether with a molecular weight of 10,000 is prepared in a 5L polymerization reactor, comprising the following steps:
[0117] (1) Add 325 g of allyl alcohol to a clean reactor, start stirring, replace with N2 three times, then add 5 g of potassium metal. Allow to react fully to completely dissolve the potassium metal. If the material temperature rises sharply or exceeds 85°C, turn on the cooling water to lower the temperature of the reactants. Add 135 g of 3-butene-1-ol.
[0118] (2) Continue N2 replacement for 2 times, maintain the pressure in the reactor slightly higher than normal pressure, then introduce propylene oxide: 2540 g, maintain the reaction temperature at 110°C, feed time 5 hours, and continue the reaction for 2.5 hours after the end of feeding until the reaction is complete.
[0119] (3) The material was completely transferred to a 5L atmospheric pressure glass reactor, 300g of deionized water was added to the reactor, the temperature was raised to 90°C for reaction for 1 hour, 25g of 85% phosphoric acid was added, the temperature was maintained for neutralization for 1.5 hours, and then the temperature was raised to 120°C, and the water in the system was completely removed by vacuum. After the water content was analyzed to be less than 0.02%, the vacuum was broken with N2, and 5g of magnesium silicate refining agent was added to the reactor, the temperature was maintained for refining for 2 hours, and the material was discharged. The solid residue was filtered with a plate circulation filter or a Buchner funnel with filter paper to obtain a polyether intermediate.
[0120] (4) Add 120 g of the polyether intermediate and 0.01 g of a 10% fluorosilicic acid aqueous solution and mix for half an hour. Then add 0.125 g of a DMC catalyst and mix thoroughly. Then put the mixture into a clean reactor and start heating, stirring, and vacuum. Raise the temperature to 145°C.
[0121] (5) Turn off the vacuum, control the reaction temperature at 140-145°C, first introduce 480 g of propylene oxide, add the feed time for 1 hour, mature for 0.5 hour, then introduce a mixture of 450 g of ethylene oxide and 1350 g of propylene oxide, add the feed time for 3 hours, mature for 0.5 hour after the addition is completed, finally add 600 g of propylene oxide, add the feed time for 1.5 hours, mature for 1 hour, then cool to 110°C and start vacuum degassing for 30 minutes to remove unreacted volatile components to obtain a crude polyether.
[0122] (6) The crude polyether was transferred to a glass neutralization reactor, cooled to below 60°C, and then 0.5 g of a 10% NaOH aqueous solution was added. The reaction temperature was maintained at 50-60°C for 1 hour for alkalization, and then 0.6 g of a magnesium silicate fine agent was added. The temperature was raised to 110°C for dehydration until the moisture content of the material was less than 0.02%, and the material was filtered twice with a G4 sand core funnel. Due to the slow filtration speed, the material liquid needed to be kept warm during the filtration process to obtain the finished polyether.
[0123] Example 4
[0124] Unsaturated polyether was prepared according to the method of Example 1, except that:
[0125] The structure of the polyether adopts all-random copolymerization.
[0126] An unsaturated polyether with a molecular weight of 10,000 is prepared in a 5L polymerization reactor, comprising the following steps:
[0127] (1) Add 325 g of allyl alcohol to a clean reactor, start stirring, replace with N2 three times, then add 5 g of potassium metal. Allow to react fully to completely dissolve the potassium metal. If the material temperature rises sharply or exceeds 85°C, turn on the cooling water to lower the temperature of the reactants. Add 135 g of 3-butene-1-ol.
[0128] (2) Continue N2 replacement for 2 times, maintain the pressure in the reactor slightly higher than normal pressure, then introduce a mixture of 2159 g propylene oxide and 381 g ethylene oxide, maintain the reaction temperature at 110°C, and feed for 5 hours. After the feeding is completed, continue the reaction for 2.5 hours until the reaction is complete.
[0129] (3) The material was completely transferred to a 5L atmospheric pressure glass reactor, 400g of deionized water was added to the reactor, the temperature was raised to 90°C for reaction for 1 hour, 25g of 85% phosphoric acid was added, the temperature was maintained for neutralization for 1.5 hours, and then the temperature was raised to 120°C, and the water in the system was completely removed by vacuum. After the water content was analyzed to be less than 0.02%, the vacuum was broken with N2, and 5g of magnesium silicate refining agent was added to the reactor, the temperature was maintained for refining for 2 hours, and the material was discharged. The solid residue was filtered with a plate circulation filter or a Buchner funnel with filter paper to obtain a polyether intermediate.
[0130] (4) Add 120 g of the polyether intermediate and 0.01 g of a 10% fluorosilicic acid aqueous solution and mix for half an hour. Then add 0.125 g of a DMC catalyst and mix thoroughly. Then put the mixture into a clean reactor and start heating, stirring, and vacuum. Raise the temperature to 145°C.
[0131] (5) Turn off the vacuum, control the reaction temperature at 140-145°C, introduce a mixture of 2450 g of propylene oxide and 430 g of ethylene oxide, add the mixture for 7.5 hours, mature for 1.5 hours, then cool to 110°C and start vacuum degassing for 30 minutes to remove unreacted volatile components to obtain a crude polyether.
[0132] (6) The crude polyether was transferred to a glass neutralization reactor, cooled to below 60°C, and then 0.5 g of a 10% NaOH aqueous solution was added. The reaction was maintained at 50-60°C for 1 hour for alkalization, and then 0.6 g of a magnesium silicate concentrate was added. The temperature was raised to 110°C for dehydration until the moisture content of the material was less than 0.02%, and the finished polyether was obtained by filter pressing with a high-purity glass fiber filter membrane.
[0133] Comparative Example 1
[0134] Unsaturated polyether was prepared according to the method of Example 1, except that:
[0135] In step (1), the initiator is only 435 g of allyl alcohol.
[0136] An unsaturated polyether with a molecular weight of 10,000 is prepared in a 5L polymerization reactor, comprising the following steps:
[0137] (1) Add 435 g of allyl alcohol to a clean reactor, start stirring, replace with N2 three times, then add 5 g of potassium metal, and allow the reaction to fully dissolve the potassium metal. If the material temperature rises sharply or exceeds 85°C, turn on the cooling water to lower the temperature of the reactants.
[0138] (2) Continue N2 replacement for 2 times, maintain the pressure in the reactor slightly higher than normal pressure, then introduce propylene oxide: 2540 g, maintain the reaction temperature at 110°C, feed time 5 hours, and continue the reaction for 2.5 hours after the end of feeding until the reaction is complete.
[0139] (3) The material was completely transferred to a 5L atmospheric pressure glass reactor, 300g of deionized water was added to the reactor, the temperature was raised to 90°C for reaction for 1 hour, 25g of 85% phosphoric acid was added, the temperature was maintained for neutralization for 1.5 hours, and then the temperature was raised to 120°C, and the water in the system was completely removed by vacuum. After the water content was analyzed to be less than 0.02%, the vacuum was broken with N2, and 5g of magnesium silicate refining agent was added to the reactor, the temperature was maintained for refining for 2 hours, and the material was discharged. The solid residue was filtered with a plate circulation filter or a Buchner funnel with filter paper to obtain a polyether intermediate.
[0140] (4) Add 120 g of the polyether intermediate and 0.01 g of a 10% fluorosilicic acid aqueous solution and mix for half an hour. Then add 0.125 g of a DMC catalyst and mix thoroughly. Then put the mixture into a clean reactor and start heating, stirring, and vacuum. Raise the temperature to 145°C.
[0141] (5) Turn off the vacuum, control the reaction temperature at 140-145°C, first introduce 480 g of propylene oxide, add the feed time for 1 hour, mature for 0.5 hour, then introduce a mixture of 450 g of ethylene oxide and 1350 g of propylene oxide, add the feed time for 3 hours, mature for 0.5 hour after the addition is completed, finally add 600 g of propylene oxide, add the feed time for 1.5 hours, mature for 1 hour, then cool to 110°C and start vacuum degassing for 30 minutes to remove unreacted volatile components to obtain a crude polyether.
[0142] (6) The crude polyether was transferred to a glass neutralization reactor, cooled to below 60°C, and then 0.5 g of a 10% NaOH aqueous solution was added. The reaction was maintained at 50-60°C for 1 hour for alkalization, and then 0.6 g of a magnesium silicate concentrate was added. The temperature was raised to 110°C for dehydration until the moisture content of the material was less than 0.02%, and the finished polyether was obtained by filter pressing with a high-purity glass fiber filter membrane.
[0143] Test Case
[0144] The molecular weight, molecular weight distribution coefficient, double bond retention rate and impurity content of the polyethers prepared in the above examples and comparative examples were tested, and the results are shown in Table 1 below.
[0145] The molecular weight and molecular weight distribution coefficient are determined according to GB / T 31816-2015;
[0146] The double bond retention rate is determined by converting the iodine value according to GB / T 13892-2020;
[0147] The metal impurity content in the product was detected by ICP analysis.
[0148] Table 1
[0149]
[0150] When allyl alcohol is used as an initiator to prepare polyether, the double bond retention rate has a significant advantage, but the reaction activity is low in the process of preparing sealants. Therefore, considering the balance between double bond retention rate and reaction activity, a compound initiator can be selected. Acidic auxiliary catalysts should be selected with certain acidity and no chemical oxidation and reduction, but organic acids should be avoided as much as possible to reduce side reactions during the polymerization process. High-purity glass fiber filter membranes have a fast filtration speed and the ability to adsorb trace metal ions. If traditional glass sand core filtration is used, the trace metal ions in the polyether need to be re-adsorbed with ultra-fine pore silica before filtration, and then filtered multiple times to ensure that the metal ion content in the polyether meets the raw material requirements of the sealant. The process is complicated.
[0151] In the description of the present application, it should be noted that the terms "upper", "lower", "inside", "outside", "front", "back", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships in the working state of the present application. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present application.
[0152] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "install", "connect" and "connect" should be understood in a broad sense. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0153] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A synthesis process for high molecular weight unsaturated polyether, characterized in that: The steps include: (1) adding a first initiator to a reaction system, replacing with an inert gas, adding a basic catalyst, reacting to completely dissolve the basic catalyst, and adding a second initiator; (2) continuing the inert gas replacement, feeding the first epoxy monomer at the first reaction temperature, and continuing the reaction until the reaction is complete after the feeding is completed to obtain a first low molecular weight polyether; (3) subjecting the first low molecular weight polyether to a water-adding and temperature-raising reaction, neutralization, water removal, and a first refining in sequence, and then discharging and filtering a solid residue to obtain a second low molecular weight polyether; (4) mixing the second low molecular weight polyether and the solution of the acidic auxiliary catalyst, then adding the double metal cyanide complex catalyst, and starting heating, stirring, and vacuum; (5) Turn off the vacuum, control the second reaction temperature, introduce epoxy monomer for aging, then cool down and perform vacuum degassing.
2. The synthesis process according to claim 1, characterized in that Step (5) obtains a crude polyether, and the synthesis process further comprises the following steps after step (5): (6) After cooling the crude polyether, alkalization, secondary refining, heating dehydration, and filtration are performed in sequence to obtain a high molecular weight unsaturated polyether.
3. The synthesis process according to claim 1, characterized in that: The acidic auxiliary catalyst in step (4) is fluorosilicic acid and / or fluoroboric acid.
4. The synthesis process according to claim 2, characterized in that: The mass fraction of the solution of the acidic auxiliary catalyst in step (4) is 5-15%, and the amount of the solution of the acidic auxiliary catalyst is 1-10 ppm of the designed total mass of the high molecular weight unsaturated polyether; The dosage of the double metal cyanide complex catalyst is 15 to 65 ppm of the designed total mass of the high molecular weight unsaturated polyether.
5. The synthesis process according to claim 1, characterized in that: In step (4), the second low molecular weight polyether and the solution of the acidic auxiliary catalyst are mixed for 20 to 60 minutes and then the double metal cyanide complex catalyst is added.
6. The synthesis process according to claim 2, characterized in that: The step (5) of introducing epoxy monomer for aging comprises the following steps performed in sequence: A second epoxy monomer is introduced to perform a first aging process, a third epoxy monomer is introduced to perform a second aging process, and a fourth epoxy monomer is introduced to perform a third aging process.
7. The synthesis process according to claim 6, characterized in that: The first epoxy monomer in step (2), the second epoxy monomer in step (5), the third epoxy monomer, and the fourth epoxy monomer are each ethylene oxide and / or propylene oxide.
8. The synthesis process according to claim 7, characterized in that: In step (2), the first epoxy monomer is propylene oxide; in step (5), the second epoxy monomer is propylene oxide, the third epoxy monomer is a mixture of ethylene oxide and propylene oxide, and the fourth epoxy monomer is propylene oxide; Based on the designed total mass of the high molecular weight unsaturated polyether, the mass proportion of ethylene oxide in the third epoxy monomer is 0 to 35%.
9. The synthesis process according to claim 2, characterized in that: In step (1), the first initiator and the second initiator are each one or more selected from allyl alcohol, methacrylic alcohol, N-methylallylamine, and 3-butene-1-ol; Based on the molecular weight of the high molecular weight unsaturated polyether being 5000-15000, the molecular weight of the first initiator accounts for 0.05-0.75% of the molecular weight of the high molecular weight unsaturated polyether, and the molecular weight of the second initiator accounts for 0.02-1.00% of the molecular weight of the high molecular weight unsaturated polyether.
10. The synthesis process according to claim 9, characterized in that: In step (1), the first initiator is allyl alcohol, and the second initiator is 3-butene-1-ol.
11. The synthesis process according to claim 2, characterized in that: The filtration in step (6) is performed by pressure filtration using a glass fiber filter membrane.
12. The synthesis process according to claim 1, characterized in that: The alkaline catalyst in step (1) is one or more selected from metallic potassium, metallic sodium, sodium methoxide, potassium hydroxide, and sodium hydroxide; The amount of the alkaline catalyst added in step (1) is 0.05 to 1.00% of the total mass of the second low molecular weight polyether added in step (3).
Citation Information
Cited By
Preparation method of silane-terminated polyether
CN122277888A